2014
DOI: 10.1371/journal.pone.0085252
|View full text |Cite
|
Sign up to set email alerts
|

MoPex19, which Is Essential for Maintenance of Peroxisomal Structure and Woronin Bodies, Is Required for Metabolism and Development in the Rice Blast Fungus

Abstract: Peroxisomes are present ubiquitously and make important contributions to cellular metabolism in eukaryotes. They play crucial roles in pathogenicity of plant fungal pathogens. The peroxisomal matrix proteins and peroxisomal membrane proteins (PMPs) are synthesized in the cytosol and imported post-translationally. Although the peroxisomal import machineries are generally conserved, some species-specific features were found in different types of organisms. In phytopathogenic fungi, the pathways of the matrix pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 71 publications
(145 reference statements)
4
93
0
Order By: Relevance
“…In M. oryzae , mutants with abnormal peroxisomes such as ΔMopex6 [30], ΔMopex5 [34], ΔMopex7 [33], and ΔMopex19 [41] showed inability to metabolize fatty acids and NaAC. In addition, yeast Δsnf1 and Δsnf4 were reported to be devoid of peroxisomal structures [38].…”
Section: Resultsmentioning
confidence: 99%
“…In M. oryzae , mutants with abnormal peroxisomes such as ΔMopex6 [30], ΔMopex5 [34], ΔMopex7 [33], and ΔMopex19 [41] showed inability to metabolize fatty acids and NaAC. In addition, yeast Δsnf1 and Δsnf4 were reported to be devoid of peroxisomal structures [38].…”
Section: Resultsmentioning
confidence: 99%
“…MoPEX7 contributes to the import of PTS2 matrix proteins30. Recently, it has been reported that the imports of PTS1- and PTS2-containing matrix proteins were impaired in the ΔMopex19 mutants31. In this study, we compared the distribution of GFP-PTS1 and PTS2-GFP in the wild-type strain and ΔMopex1 mutants.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we also transformed GFP-PMP47, a fusion representing the integral peroxisomal membrane proteins31, into the wild-type strain and ΔMopex1 mutants. Although the florescence was generally in punctate pattern, diffuse florescence could be detected in the conidia of the ΔMopex1 /GFP-PMP47, in contrast to the absolute punctate pattern in the wild type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations